2015
DOI: 10.3389/fonc.2015.00037
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer and Neuroendocrine Differentiation: More Neuronal, Less Endocrine?

Abstract: Neuroendocrine differentiation (NED) marks a structural and functional feature of certain cancers, including prostate cancer (PCa), whereby the malignant tissue contains a significant proportion of cells displaying neuronal, endocrine, or mixed features. NED cells produce, and can secrete, a cocktail of mediators commonly encountered in the nervous system, which may stimulate and coordinate cancer growth. In PCa, NED appears during advanced stages, subsequent to treatment, and accompanies treatment resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
76
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 211 publications
(358 reference statements)
6
76
0
Order By: Relevance
“…MED12L/MED12 are components of the mediator complex and important regulators of the WNT pathway, which has been implicated in cell proliferation and neuroendocrine differentiation in PCa22232425. The MED12L / MED12 axis is implicated in metastatic sporadic PCa, with MED12 nuclear overexpression common in mCRPC and localized recurrent PCa but not in localized primary PCa or benign prostate tissue26.…”
Section: Discussionmentioning
confidence: 99%
“…MED12L/MED12 are components of the mediator complex and important regulators of the WNT pathway, which has been implicated in cell proliferation and neuroendocrine differentiation in PCa22232425. The MED12L / MED12 axis is implicated in metastatic sporadic PCa, with MED12 nuclear overexpression common in mCRPC and localized recurrent PCa but not in localized primary PCa or benign prostate tissue26.…”
Section: Discussionmentioning
confidence: 99%
“…In low invasive LNCaP cells, β-adrenergic stimulation induces the acquisition of a highly malignant neuroendocrine (NE) phenotype. NE prostate tumors exhibit neurite-like (NE-like) projections; they synthesize and secrete amines and peptides, are androgenreceptor negative and apoptosis resistant (8,9,13,14). In humans, β2-adrenergic receptors (ADR-β 2) are highly expressed in androgen-refractory metastatic tumors and are strongly associated with for 3-5 years with adrenergic antagonists (2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…NE cancer cells have been considered as non-proliferative, postmitotic cells located adjacent to proliferative Bcl-2-positive cells [13,85]. NED areas exhibited the highest proliferation index across tumor tissue and the extent of NED correlated with a higher proliferation index of the whole tumor [86,87]. It was further shown that NE cancer cells secrete growth stimulating peptides (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that the extent of neuroendocrine differentiation (NED) correlates with exposure to ADT and represents an adaptive clinical phenotype, which is of special significance regarding the advent of novel highly potent AR-targeted therapies [75,[77][78][79][80][81][82][83][84][85][86]. Androgen-deprived culture conditions were shown to induce a neuronal morphology and expression of NSE and CHGA in LNCaP cells [87]. Intriguing molecular mechanisms of ADT-induced NED in PCa have recently been elucidated (Table 1.1).…”
Section: Neuroendocrine Prostate Cancermentioning
confidence: 99%